Pro Oracle Database 11g Administration - Kuhn, Darl.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2010)
Pro Oracle Database 11g Administration is a book focused on results. Author Darl Kuhn draws from a well of experience over a decade deep to lay out real-world techniques that lead to success as an Oracle Database administrator. He gives clear explanations on how to perform critical tasks. He weaves in theory where necessary without bogging you down in unneeded detail. He is not afraid to take a stand on how things should be done. He won$1 (Bt leave you adrift in a sea of choices, showing you three ways to do something and then walking away. Database administration isn$1 (Bt about passing a certified exam, or about pointing-and-clicking your way through a crisis. Database administration is about applying the right solution at the right time, about avoiding risk, about making robust choices that get you home each night in time for dinner with your family. If you have (3z(Bbuck stops here(3y (Bresponsibility for an Oracle database, then Pro Oracle Database 11g Administration is the book you need to help elevate yourself to the level of Professional Oracle Database Administrator. Condenses and organizes the core job of a database administrator into one volume. Takes a results-oriented approach to getting things done. Lays a foundation upon which to build a senior level of expertises
1 Installing the Oracle Binaries -- 2 Implementing a Database -- 3 Configuring an Efficient Environment -- 4 Tablespaces and Datafiles -- 5 Managing Control Files and Online Redo Logs -- 6 Users and Basic Security -- 7 Tables and Constraints -- 8 Indexes -- 9 Views, Synonyms, and Sequences -- 10 Data Dictionary Basics -- 11 Large Objects -- 12 Partitioning: Divide and Conquer -- 13 Data Pump -- 14 External Tables -- 15 Materialized Views -- 16 User-Managed Backup and Recovery -- 17 Configuring RMAN -- 18 RMAN Backups and Reporting -- 19 RMAN Restore and Recovery -- 20 Oracle Secure Backup -- 21 Automating Jobs -- 22 Database Troubleshooting.
Keywords: Computer science; Database management; Computer Science; Database Management